PENGARUH MODAL INTELEKTUAL TERHADAP EFISIENSI OPERASIONAL PERUSAHAAN MANUFAKTUR (Studi Empiris pada Perusahaan manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2019) - Rahadiansyah, Arief; Dewayanto, Totok (Diponegoro Journal of Accounting, 2021)
Global business competition is currently very tight, so companies are required to provide new innovations in order to remain competitive in the market. This forces the company to have highly intellectual human resources. Because to remain competitive in the market the company must be able to provide products that have the same quality as in the market but at a lower price than the market, so the company must be able to produce low operating costs in order to reduce the selling price in the market. This study aims to test the M-VAIC, HCE, RCE, and CEE hypotheses on the company's operational efficiency. The method used in this study is purposive sampling with a total sample of 101 research samples in the manufacturing sector listed on the Indonesia Stock Exchange in 2016-2019. The analysis technique used is multiple regression and using a cross-section data model. The results of this study indicate that RCE and CEE have a significant positive relationship to the company's operational efficiency.